A Comparative Study on Different Effects and Exposure Duration Between Conventional Cigarette Smoke and Electronic Cigarette Vapor on Serum Interleukin-1? Level: An In Vivo Study - Christantia, Vienna; Budianto, Iskandar Rahardjo; Djuartina, Tena; Handayani, Maria Dara Novi (Jurnal Veteriner; Vol 23 No 2 (2022)DO - 10.19087/jveteriner.2022.23.2.252, 2022)
Smoking is known to have bad effects on health. People start using e-cigarettes with the assumption that e-cigarettes are safer, but the safety of e-cigarettes is still in doubt. Harmful substances from cigarettes can trigger an increase in free radicals and induce inflammatory process. The aim of this study was to evaluate and compare the increase of serum Interleukin-1? due to exposure to conventional cigarette smoke and e-cigarette vapor based on exposure time. This study was conducted experimentally on 30 male white rats Sprague Dawley strain. The rats were divided into five treatment groups (control group, two and four weeks of exposure to conventional cigarette smoke, and two and four weeks of exposure to electronic cigarette vapor). Smoking session was given once a day. The rats were sacrificed then necropsied and Interleukin-? levels were calculated using the enzyme linked immunosorbent assay (ELISA) Kit. The data obtained were analyzed using one-way analysis of variance (ANOVA) statistical test. Exposure to conventional cigarette smoke and e-cigarette vapor did not give any significant changes to Interleukin-1? level in rats, both at two weeks and four weeks of exposure. However, there was a tendency of increased Interleukin-1? levels with increasing time. This tendency is more obvious in groups with exposure to conventional cigarette.